PERADILAN PIDANA TERPADU BERDASARKAN RUU KUHAP - -, SUPRIYANTA (Wacana Hukum, 2010)
AbstratsIn order to achieve the integrated criminal justice, there are several rules about the functional integration between the sub-system of investigation and the sub-system of prosecution which has already been stated on RUU KUHAP. If the investigator come to the condition when the case that he carried out did not have adequate evidence or the investigated case was proved that it was not a criminal act or the investigation was stopped by the law, the investigator by the prosecutor approval should terminate the investigation and reported that termination to the prosecutor, suspect,  complainant, victim or his/her relatives within two days. Keywords: RUU KUHAP, integrated criminal justice.